Successful treatment of out-of-hospital cardiac arrest is still based on quick activation of the chain of survival - Borgstedt, Laura; Schaller, Stefan J.; Goudkamp, Daniel; Fuest, Kristina; Ulm, Bernhard; Jungwirth, Bettina; Blobner, Manfred; Schmid, Sebastian (Frontiers in Public Health, 2023)
Background and Goal of Study: Cardiopulmonary resuscitation (CPR) in prehospital settings is a major reason for emergency medical service (EMS) dispatches. CPR outcome depends on various factors, such as bystander CPR and initial heart rhythm (1). Our aim was to investigate whether short-term outcome or performance of CPR differ depending on the location of the out-of-hospital cardiac arrest and assess factors associated with return of spontaneous circulation (ROSC) in patients with out-of-hospital cardiac arrest (OHCA). Materials and Methods: After approval of the ethics committee of the TUM School of Medicine (508/16), protocols of a prehospital physician staffed emergency service (EMS) located in Munich-Riem were retrospectively evaluated using Mann-Whitney-U test, chi square test, and a multifactor logistic regression model. Results and Discussion: Of 12,073 cases between January 1st, 2014 – December 31st, 2017, 723 EMS responses with out-of-hospital cardiac arrest were analysed. In 393 of these cases CPR was performed. The incidence of ROSC did not differ between public or non-public space (p = 0.4) but patients with OHCA in public space were more often admitted to the hospital with spontaneous circulation (p = 0.011). Shockable initial rhythm was not different between locations (p = 0.2) but defibrillation was performed significantly more often in public places (p < 0.001). Multivariate analyses showed that hospital admission with spontaneous circulation was more likely in patients with shockable initial heart rhythm (p < 0.001) and if CPR was started by an emergency physician (p = 0.006). Conclusions: The incidence of ROSC did not differ between locations. Shockable initial heart rhythm, defibrillation, and start of resuscitative efforts by an emergency physician were associated with higher chances of hospital admission with spontaneous circulation. Bystander CPR and the use of bystander automated external defibrillators (AED) was overall low. This study shows that activation of the chain of survival in OHCA as early as possible is associated with successful CPR in terms of sustained ROSC at hospital admission. Also, education in basic life support as well as bystander AED use in the general population are still of paramount importance in order to strengthen the chain of survival.